Governance, institutions, and climate change resilience in Sub-Saharan Africa: assessing the threshold effects - Bambi, Prince Dorian Rivel; Batatana, Marly Loria Diabakanga; Appiah, Michael; Tetteh, Derrick (Frontiers in Environmental Science, 2024)
The concerns about institutional weakness in Sub-Saharan Africa (SSA) are central to the discussion on environmental degradation in the region. This study employs a robust dynamic panel data estimator to explore the relationships between institutions, governance, and environmental quality, focusing on the ecological footprint of 25 SSA nations from 1990 to 2020. The results reveal the threshold effects of the interaction between institutions and governance, following an inverted U-shape pattern. This suggests that beyond a certain ecological footprint, increased interaction between institutions and governance leads to a decrease in ecological footprint. Additionally, high institutional quality (IQ) is associated with a lower environmental impact, while improved governance contributes to mitigating the decline in institutional performance. The panel causality tests among the variables and control components indicate a oneway causal relationship from ecological footprint to governance, infrastructural development, and energy use.Conversely, a feedback causal relationship exists between IQ, industrialization, and ecological footprints.Policymakers should prioritize investments in energy consumption that align with environmental quality, ensuring efficient use of energy budgets through coordinated planning, execution, and transfer of sound energy practices to prevent duplication of efforts.